PENGEMBANGAN MEDIA ACROSS SMART PADA MATERI BILANGAN BULAT UNTUK SISWA KELAS IV SD MUHAMMADIYAH NGUPASAN 2 YOGYAKARTA - Saputro, Hengkang Bara; Sari, Vera Fadhela (Mathematics Education And Application Journal (META), 2023)
The aim of this research is to determine the steps for developing Across Smart mathematics media and determine the feasibility of learning media Across Smart mathematics with integer material for fourth grade elementary school students. The research method used is research and development with the borg and gall model. The small group trial was carried out at SD N Muhammadiyah Ngupasan 2 Yogyakarta with a total of 23 students. The data analysis techniques of this research are qualitative data and quantitative data. The qualitative data in this research is in the form of criticism and suggestions from material experts, learning evaluation experts, teachers and students. The quantitative data in this research is in the form of expert, teacher and student assessments. Based on the research results, assessment data was obtained from material experts with an average score of 92.7 "very appropriate", assessments from learning experts with an average value of 92 "very appropriate", assessments from language experts with an average value of 80 "very appropriate" , and an assessment from media experts with an average score of 86.2 "very feasible", the quality of Across Smart media development in mathematics learning on integer material obtained an average assessment of 87.7 in the "very feasible" category, an assessment from students with an average score of 90.91 in the "very decent" category. The assessment obtained shows that the development of Across Smart media in learning mathematics with integer material for class IV students is quality, feasible and effective for use.Keywords: Across Smart, Mathematics, Media Tujuan penelitian ini yaitu untuk mengetahui langkah-langkah pengembangan media Across Smart matematika dan mengetahui kelayakan media pembelajaran Across Smart matematika materi bilangan bulat untuk siswa kelas IV SD. Metode penelitian yang digunakan adalah penelitian dan pengembangan dengan model borg and gall. Uji coba kelompok kecil dilaksanakan di SD N Muhammadiyah Ngupasan 2 Yogyakarta dengan jumlah 23 siswa. Teknik analisis data dari penelitian ini adalah data kualitatif dan data kuantitatif. Data kualitatif dalam penelitian ini berupa kritik dan saran ahli materi, ahli evaluasi pembelajaran, guru dan siswa. Data kuantitatif dalam penelitian ini berupa hasil penilaian ahli, guru dan siswa. Berdasarkan hasil peneitian diperoleh data penilaian dari ahli materi dengan rata-rata nilai 92,7 “sangat layak”, penilaian dari ahli pembelajaran rata-rata nilai 92 “sangat layak”, penilaian dari ahli bahasa dengan rata-rata nilai 80 “sangat layak”, dan penilaian dari ahli media dengan rata-rata nilai 86,2 “sangat layak”, kualitas pengembangan media Across smart dalam pembelajaran matematika pada materi bilangan bulat memperoleh penilaian rata-rata 87,7 dengan kategori “sangat layak”, penilaian dari peserta didik dengan rata-rata nilai 90,91 dengan kategori “sangat layak”. Penilaian yang diperoleh menunjukkan bahwa pengembangan media Across Smart dalam pembelajaran matematika materi bilangan bulat untuk siswa kelas IV berkualitas, layak dan efektif untuk digunakan.Kata kunci: Across Smart,  Matematika, Media